Band structure and transmission characteristics of onedimensional photonic crystal composed with singlenegative materials - Thapa K.B.; Singh P.P.; Kumar N.; Ojha S.P. (My University, 2025)
Band structure and transmittance characteristics of one-dimensional photonic crystal composed with single negative materials (MNG and ENG) are studied by using simple transfer matrix method and Bloch theorem. The band structure and the transmittance for TE and TM-modes are studied for the structure with MNG and different values of electric permittivity (ε) when ENG and magnetic permeability (μ) is constant and vice-versa. To obtain a large band gap, the structure should have high ε and MNG with large thickness, and high ε and ENG with small thickness. The study of the transmittance shows the tunneling property of electromagnetic wave due to presence of zero- ε and zero- μ. The existence of zero-ε and zero-μ are revealed due to the band gap is not found in the same frequency range for the transmittance. Besides this, we have studied the transmittance of the structure of MNG-ENG with different values of ε and μ, angles of incidence, and thicknesses. By choosing proper thick ness of the structure and angle of incidence, a large omni-directional band gap can be achieved, which can be used as a filter.